The Use of Word Mapping to Activate Students’ Verbal Participation in Teaching Speaking at Tour and Travel Department of Vocational High School - Vischa Mansyera Pratama; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2018)
This article aimed to describe the use of word mapping technique in teaching speaking for Tour and Travel Department Students of Vocational High School. Word mapping is a technique in teaching speaking that can engage students to speak intensively and to share their ideas in a fun way. This technique can be done by group and individual. Word Mapping is a technique that can motivate the students to share their ideas and speak in the teaching and learning process in describing tourism object and tourism destination. Word Mapping is a suitable technique that can be used in teaching speaking to tour and travel department students in vocational high school. It is an important technique that improves the way to record information, supports ideas, and enhances creative problem solving as they hold information in a format that the students’ mind finds easy to remember and quick to review. It makes easier for the students to share their ideas in speaking. Therefore, students will more active in teaching and learning process and give the good response to the material and topic that is taught by the teacher.